Epstein–Barr virus LMP1 oncogene polymorphism in tatar and slavic populations in Russian Federation impacting on some malignant tumours - V. E. Gurtsevitch (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Objective: To compare genetic structure of the main Epstein–Barr virus (EBV) oncogene, latent membrane protein 1 (LMP1), in EBV strains circulating in two genetically distinct ethnic populations in Russian Federation, Tatars and Slavs, as well as assess an impact of diverse LMP1 variants on incidence and mortality rate for some malignant tumors partially associated with EBV infection. Materials and methods. Oral washing samples were collected from 60 ethnic Kazan Tatars and 65 ethnic Moscow Slavics. Carboxy-terminal nucleotide sequences (41 and 40 sequences, respectively) derived from hypervariable LMP1 gene region were amplified from EBV DNA samples. Next, final nucleotide sequences were translated into amino acid sequences and analyzed according to classification by Edwards et al. Results. Analysis of 41 and 40 LMP1 samples obtained from ethnic Kasan Tatars and ethnic Moscow Slavics, respectively, revealed significant difference in relevant amino acid structures. In particular, all LMP1 samples derived from Moscow Slavics were found to belong to the four protein variants: B95.8/A, Med–, China1 and NC. Among them, low-transforming variant B95.8/A was dominant (82.5%). In contrast, solely 21 out of 41 LMP1 samples derived from ethnic Tatars were classified as B95.8/A, Med– and China1 variants. Importantly, the percentage of low-transforming B95.8/A variant among ethnic Tatar samples was significantly lower compared to that one found in Moscow Slavics (29.3% vs. 82.5%). On the other hand, seven (17.1%) out of 20 other samples formed a unique protein mono group characterized by LMP1 amino acid sequence differed from that one available in the GenBank database. Such group of variants was designated as LMP1-TatK. The remaining 13 samples (31.7%) did not match either protein variants, thereby forming the “beyond classification” (LMP1-TatBC) group. Conclusion. The data obtained suggest that various LMP1 variants exist in EBV strains persisting in ethnic Tatrs and ethnic Slavics examined in Russian Federation. It was also found that EBV strains isolated from ethnic Tatars contained a unique LMP1 gene variant encoding protein LMP1-TatK lacked in EBV strains derived from ethnic Moscow Slavics. Taking into account the genealogy of Tatars, it cannot be ruled out that EBV strain bearing LMP1-TatK variant represented ethnically specific EBV strain that might circulate many centuries ago among their historical human predecessors called Mongol-Tatar tribes. In addition, it was shown that the LMP1 variants in EBV strains isolated from ethnic Kazan Tatars and ethnic Moscow Slavics did not affect the incidence and mortality of different forms of cancer consisting of EBV-associated cases.